Functional ultrasound detects frequency-specific acute and delayed S-ketamine effects in the healthy mouse brain - Ionescu, Tudor M.; Grohs-Metz, Gillian; Hengerer, Bastian (Frontiers in Neuroscience, 2023)
S-ketamine has received great interest due to both its antidepressant effects and its potential to induce psychosis when administered subchronically. However, no studies have investigated both its acute and delayed effects using in vivo small-animal imaging. Recently, functional ultrasound (fUS) has emerged as a powerful alternative to functional magnetic resonance imaging (fMRI), outperforming it in sensitivity and in spatiotemporal resolution. In this study, we employed fUS to thoroughly characterize acute and delayed S-ketamine effects on functional connectivity (FC) within the same cohort at slow frequency bands ranging from 0.01 to 1.25Hz, previously reported to exhibit FC. We acquired fUS scans in a total of 16 healthy C57/Bl6 mice split in two cohorts (n=8 received saline, n=8 S-ketamine). After assessing reproducibility and reliability of the FC readouts at baseline in six frequency bands, we investigated the acute, subacute and subchronic effects of S-ketamine for all bands by performing a total of four fUS measurements in both cohorts. We found reproducible (r > 0.9) and reliable (r > 0.9) group-average readouts in all frequency bands, only the slow5 band (0.01-0.027Hz) performing slightly worse. Acute effects showed strong FC increases in five of the six bands, peaking in the slow3 band (0.073-0.2Hz) and, intriguingly, robust corticostriatal FC decreases in the fastest band, slow1-2 (0.75Hz-1.25Hz). These changes at slow1-2 persisted to a weaker extent after 24 hours and were accompanied by cortical FC decreases across the other bands. Subchronically, the decreases in slow1-2 were maintained, however no changes between cohorts could be detected in any other bands. Our study reveals contrasting acute and delayed effects of S-ketamine administration, while also recommending the frequency-specific analysis of FC using fUS for a more detailed delineation of pharmacological effects.